Perceptions of health professionals in providing care for people with anorexia nervosa and bulimia nervosa: a systematic review and meta-synthesis of qualitative studies - Bruna Bortolozzi Maia; Felipe Gonçalves Campelo; Elaine Campos Guijarro Rodrigues; Érika Arantes Oliveira-Cardoso; Manoel Antonio dos Santos (Cadernos de Saúde Pública, 2023)
Abstract: This study sought to synthesize and reinterpret findings from primary qualitative studies on the experience of health professionals in caring for people with anorexia nervosa and bulimia nervosa. We conducted a systematic review of the literature with the SPIDER search strategy assessing six databases. A meta-synthesis was performed with data from qualitative studies. Two independent reviewers screened and assessed the articles, extracted data from the articles and elaborated thematic synthesis. Nineteen articles met the inclusion/exclusion criteria. The meta-synthesis revealed three descriptive themes: Going outside the comfort zone: hard relational experiences of health professionals in providing care for people with anorexia nervosa and bulimia nervosa; Reflecting on treatment: relevance of discussion, communication, and flexibility in health professionals’ work with anorexia nervosa and bulimia nervosa; and Dealing with ambivalences: experiences of health professionals with family members of people with anorexia nervosa and bulimia nervosa. We elaborated two analytical themes: Making work with eating disorders palatable: malleability necessary for health professionals in bonding with people with anorexia and bulimia nervosa and their families; and Leaving the professional comfort zone: transition from multi to interdisciplinary. Thus, mental health professionals who work with people diagnosed with anorexia and bulimia nervosa cope with hard emotional experiences that makes them feel out of their comfort zone, requiring flexibility to benefit a good therapeutic alliance, but there are still difficulties in promoting interdisciplinarity.